Engaging the online learner : activities and resources for creative instruction - Conrad, Rita-Marie.; Donaldson, J. Ana. (San Francisco, Calif. : Jossey-Bass, 2004)
This book consists of two parts. Part one provides a basic framework with which to organize activities so that engagement is introduced into the online environment and learned by community members in phases. Part two presents activities that can be used to promote engagement among online learners on a phase-by-phase basis.
Preface -- The authors -- Part 1. Constructing activities to engage online learners. 1. Engaged learning in an online environment -- 2. Designing online engagement -- 3. Measuring online engaged learning -- Part 2. Activities to engage online learners. 4. Learning to use online tools -- 5. Online icebreakers -- 6. Peer partnership and team activities -- 7. Reflective activities -- 8. Authentic activities -- 9. Games and simulations -- 10. Learner-led activities -- References -- Index.
Includes bibliographical references (p. 121-123) and index.
Keywords: Internet in education -- United States; Web-based instruction -- United States; Computer-assisted instruction -- United States; Computers